2010
DOI: 10.1177/0888406409357013
|View full text |Cite
|
Sign up to set email alerts
|

Providing Immediate Feedback to Co-Teachers Through Bug-in-Ear Technology: An Effective Method of Peer Coaching in Inclusion Classrooms

Abstract: More children with special needs are educated in general education classrooms than ever before. Ideally, special education and general education teachers work together in these settings as instructional teams, but a "one teaching, one assisting" model is often in place with the special education teacher assuming a subordinate role. As such, the authors conducted research to determine whether changes can be made in teacher instruction so that both teachers in a collaborative team are highly engaged in the instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 22 publications
8
102
1
2
Order By: Relevance
“…Four articles from a behaviouristic point of view investigated feedback via bug-in-the-ear technology and its effects on (student) teachers' teaching behaviours (Goodman et al, 2008; Scheeler et al, 2010Scheeler et al, , 2012Scheeler & Lee, 2002). All of them concluded that immediate feedback is effective, and, in addition, Goodman et al (2008) and Scheeler et al (2010) advised that feedback should be specific and corrective. An overwhelming majority of these (student) teachers showed 90-100% of the desired behaviour in short term and in the 2010 study, Scheeler et al's participants showed their desired behaviour in the long term as well as in other situations in 75-100% of the cases.…”
Section: Behaviourismmentioning
confidence: 99%
See 2 more Smart Citations
“…Four articles from a behaviouristic point of view investigated feedback via bug-in-the-ear technology and its effects on (student) teachers' teaching behaviours (Goodman et al, 2008; Scheeler et al, 2010Scheeler et al, , 2012Scheeler & Lee, 2002). All of them concluded that immediate feedback is effective, and, in addition, Goodman et al (2008) and Scheeler et al (2010) advised that feedback should be specific and corrective. An overwhelming majority of these (student) teachers showed 90-100% of the desired behaviour in short term and in the 2010 study, Scheeler et al's participants showed their desired behaviour in the long term as well as in other situations in 75-100% of the cases.…”
Section: Behaviourismmentioning
confidence: 99%
“…As Table 3 shows, from a behaviouristic perspective (Goodman et al, 2008;Rodriguez et al, 2009;Scheeler et al, 2010Scheeler et al, , 2012Scheeler & Lee, 2002), feedback should be given immediately and/or timely (Auld et al, 2010). In addition, Van der Kleij et al (2012; from social constructivism) described that feedback can be provided immediate or delayed.…”
Section: Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…Side-by-side coaching has also been reported to be effective for improving students' behavior. Shanley and Niec (2010) Bug-in-ear coaching has also been shown to increase teachers' implementation of the successful three-term-contingency teaching units across a range of academic subjects (Scheeler et al, 2010). They used a multiple baseline across participants design to demonstrate that bug-in-ear technology with three general education and special education teacher pairs was successful in improving the percentage of correct implementation of three-term-contingency trials.…”
Section: Research On Side-by-side Coachingmentioning
confidence: 99%
“…Side-by-side coaching is described as a process where an expert, but not a direct supervisor, observes the teacher implementing the target practice, provides feedback in vivo, and may even model the practice with the students while the teacher observes (Kretlow & Bartholomew, 2010). Bug-in-ear coaching is similar to side-by-side coaching; however feedback is provided through wireless headsets to prevent disrupting the flow of the lesson (Scheeler, Congdon, & Stansbery, 2010).…”
Section: Coachingmentioning
confidence: 99%